SPEECH CULTURE AND ART OF ORATOTRY (Journal of Universal Science Research, 2023)
In its gnoceological aspect "speech culture" is a special area of linguistic knowledge, a scientific discipline containing definite units, subunits and rules devoted to that field of linguistics